2019
DOI: 10.1021/acs.jpcc.9b03131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbonate Anions on Quaternary Ammonium-Hydroxide Interaction

Abstract: Currently, there are two main challenges in state-of-the-art anion-exchange membrane fuel cells (AEMFCs)first, cation degradation in the presence of hydroxide anions; second, carbonation process during AEMFC operation. Both degradation and carbonation processes lead to a significant decrease in the ionic conductivity of the anion exchange membranes (AEMs), and, in turn, in the AEMFC performance. In this work, we use molecular dynamics simulations to bring first insights into the contributing factors that lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…44 The hydration of the ionomers is in part governed by the affinity of water for the cation/anion ion-pair at low RH and energy to dissociate the ions, i.e., cationic quaternary ammonium (QA) and the mobile anion, at high RH. 60 The degree of affinity of water toward the anion and cation of an ion-pair influences the hydration characteristics under drier conditions. The Hofmeister series suggests that large anions such as Br − and HCO 3 − and large cations such as QA + exhibit weak interaction with water whereas small anions such as F − and OH − and cations such H + and Li + strongly interact with water.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…44 The hydration of the ionomers is in part governed by the affinity of water for the cation/anion ion-pair at low RH and energy to dissociate the ions, i.e., cationic quaternary ammonium (QA) and the mobile anion, at high RH. 60 The degree of affinity of water toward the anion and cation of an ion-pair influences the hydration characteristics under drier conditions. The Hofmeister series suggests that large anions such as Br − and HCO 3 − and large cations such as QA + exhibit weak interaction with water whereas small anions such as F − and OH − and cations such H + and Li + strongly interact with water.…”
Section: Resultsmentioning
confidence: 99%
“…However, a MD simulation study has shown that at a hydration level of up to λ equal to 4, QA + HCO 3 − do not dissociate. 60 In the contact pair regime (λ < anion solvation number), the enthalpic term of hydration Gibbs energy would arise from the exothermic effect of mobile water attaining a less energetic state of sorbed water. For our experiments, the comparison between three forms can be done for λ of 2 or less and between F − and HCO 3 − forms for λ up to 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant progress has been achieved recently in the field of anion exchange membrane fuel cells (AEMFCs). [1][2][3] In spite of the remarkable development of this technology, the deployment of AEMFCs is still hindered by the chemical degradation of the anion exchange membrane (AEM) and ionomers, [4][5][6][7][8][9][10][11] carbonation issues, [12][13][14][15] and by the sluggish kinetics of the hydrogen oxidation reaction (HOR). [2,16,17] It has been shown that the HOR kinetics in alkaline media is two to three orders of magnitude lower than that in acidic media, [18,19] even for the most active catalysts such as Pt, [17,[19][20][21][22] Rh, [23] and Ir.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has been interested in the synthesis, and decomposition, of QAs in order to try to open new directions in the development of stable cations for AEMFCs. We have recently developed an improved procedure for the synthesis of N,N ‐diaryl carbazolium salts, which allows for the synthesis of a variety of derivatives with different substituents in very few synthetic steps and significantly better yields .…”
Section: Introductionmentioning
confidence: 99%